Pengaruh Persepsi Guru dan Kompetensi Pedagogik Terhadap Pelaksanaan Penilaian Portofolio di Lembaga PAUD Kota Bandar Lampung - Dian Rahma Putri; Undang Rosidin; Nopiana Nopiana (IJIGAEd: Indonesian Journal of Islamic Golden Age Education, 2026)
This study aims to examine the influence of early childhood teachers' perceptions of portfolio assessment and their pedagogical competence on the implementation of portfolio assessment in early childhood education institutions in Bandar Lampung. This research employs a quantitative approach with the Ex Post Facto method. The population consists of eight kindergarten institutions in Tanjung Karang Pusat District, Bandar Lampung, with a total sample of 49 teachers selected using a saturated sampling technique. Data were collected through questionnaires and observations using instruments validated by expert lecturers. The data analysis technique applied is multiple linear regression. The results show an F-value of 6.624, which is greater than the F-table value of 3.24, with a significance level (sig.) of 0.003, which is less than α = 0.05. These findings indicate that the alternative hypothesis (Ha) is accepted, meaning that early childhood teachers' perceptions of portfolio assessment and their pedagogical competence simultaneously have a positive and significant influence on the implementation of portfolio assessment in early childhood education institutions in Bandar Lampung.